Development of a Light Intensity Monitoring System in Broiler Chicken Coops Based on Arduino IoT Cloud - Habibuddin, Julianti; Azis, Muhammad Fadli; Azis, Nuritasari (Politeknik Negeri Ujung Pandang, 2024)
The lighting system significantly influences the growth and productivity of broiler chickens, necessitating an efficient tool for monitoring light intensity in chicken coops. This study aims to design and develop an Arduino IoT Cloud-based light intensity monitoring system for broiler chicken coops. The system employs two BH1750 light sensors, positioned inside and outside the coop, to measure light intensity, which is then processed by an ESP32 microcontroller. The collected data is displayed on a 16x2 LCD screen and uploaded in real time to the Arduino IoT Cloud platform for remote monitoring. Testing conducted over a 6-hour period revealed that light intensity inside the coop remained stable at approximately 30 lux from 09:30 to 12:52, while the highest external light intensity reached 400 lux between 12:06 and 14:40, followed by a decrease after 14:50. These findings indicate that the system can assist farmers in timely actions, such as opening or closing coop curtains, through effective monitoring via the Arduino IoT Cloud platform.